90-day Readmission Rates for Single Level Anterior Lumbosacral Interbody Fusion: A Nationwide Readmissions Database Analysis. Issue 14 (15th July 2020) - Elia, Christopher J.; Arvind, Varun; Brazdzionis, James; von Glinski, Alexander; Schell, Benjamin A.; Pierre, Clifford A.; Ogunlade, John; Chapman, Jens R.; Oskouian, Rod J.
Abstract : Study Design: Nationwide Readmissions Database Study. Objective: To investigate the patterns of readmissions and complications following hospitalization for elective single level anterior lumbobsacral interbody fusion. Summary of Background Data: Lumbar interbody spine fusions for degenerative disease have increased annually in the United States, including associated hospital costs. Anterior lumbar interbody fusions (ALIFs) have become popularized secondary to higher rates of fusion compared with posterior procedures, and preservation of posterior elements. Prior national databases have sought to study readmission rates with some limitations due to older diagnosis and procedure codes. The newer 2016 International Classification of Diseases Tenth Revision, Clinical Modification (ICD-10 CM) includes more specification of the surgical site. Methods: We utilized the 2016 United States Nationwide Readmissions Database (NRD), this nationally representative, all-payer database that includes weighted probability sample of inpatient hospitalizations for all ages. We identified all adults (≥ 18 yrs) using the 2016 ICD-10 coding system who underwent elective primary L5-S1 ALIF and examined rates of readmissions within 90 days of discharge. Results: Between January and September 2016, a total of 7029 patients underwent elective stand-alone L5-S1 ALIF who were identified from NRD of whom 497 (7.07%) were readmitted within 90 days of their procedure. No differences in sex were appreciated. Medicare patients had statistically significant higher readmission rates (47.69%) among all payer types. With respect to intraoperative complications, vascular complications had statistically significant increased odds of readmission (OR, 3.225, 95% CI, 0.59 –1.75; P = 0.0001). Readmitted patients had higher total healthcare costs. Conclusion: The 90-day readmission rate following stand-alone single level lumbosacral (L5-S1) ALIF was 7.07%. ALIF procedures have increased in frequency, and an understanding of the comorbidities, age-related demographics, and costs associated with 90-day readmissions are critical. Surgeons should consider these risk factors in preoperative planning and optimization. Level of Evidence: 3 Abstract : Using the 2016 US Nationwide Readmissions Database to study the 90-day readmissions for elective single level anterior lumbobsacral interbody fusion in adults. Overall 90-day readmission rate was 7.07%. Medicare patients had statistically significant higher readmission rates. Vascular complications had increased odds of readmission. Readmitted patients had higher total healthcare costs.